Site‐Targeted Interfacial Solid‐Phase Chemistry: Surface Functionalization of Organic Monolayers via Chemical Transformations Locally Induced at the Boundary between Two Solids. (5th September 2016) - Maoz, Rivka; Burshtain, Doron; Cohen, Hagai; Nelson, Peter; Berson, Jonathan; Yoffe, Alexander; Sagiv, Jacob
Abstract: Effective control of chemistry at interfaces is of fundamental importance for the advancement of methods of surface functionalization and patterning that are at the basis of many scientific and technological applications. A conceptually new type of interfacial chemical transformations has been discovered, confined to the contact surface between two solid materials, which may be induced by exposure to X‐rays, electrons or UV light, or by the application of electrical bias. One of the reacting solids is a removable thin film coating that acts as a reagent/catalyst in the chemical modification of the solid surface on which it is applied. Given the diversity of thin film coatings that may be used as solid reagents/catalysts and the lateral confinement options provided by the use of irradiation masks, conductive AFM probes or stamps, and electron beams in such solid‐phase reactions, this approach is suitable for precise targeting of different desired chemical modifications to predefined surface sites spanning the macro‐ to nanoscale.